Elucidating the process mechanism in Mg-to-Al friction stir lap welding enhanced by ultrasonic vibration - Ming Zhai; Lei Shi; ChuanSong Wu (Journal of Magnesium and Alloys)
The composite structures/components made by friction stir lap welding (FSLW) of Mg alloy sheet and Al alloy sheet are of wide application potentials in the manufacturing sector of transportation vehicles. To further improve the joint quality, the ultrasonic vibration (UV) is exerted in FSLW, and the UV enhanced FSLW (UVeFSLW) was developed for making Mg-to-Al dissimilar joints. The numerical analysis and experimental investigation were combined to study the process mechanism in Mg/Al UVeFSLW. An equation related to the temperature and strain rate was derived to calculate the grain size at different locations of the weld nugget zone, and the effect of grain size distribution on the threshold thermal stress was included, so that the prediction accuracy of flow stress was further improved. With such modified constitutive equation, the numerical simulation was conducted to compare the heat generation, temperature profiles and material flow behaviors in Mg/Al UVeFSLW/FSLW processes. It was found that the exerted UV decreased the temperature at two checking points on the tool/workpiece interface from 707/671 K in FSLW to 689/660 K in UVeFSLW, which suppressed the IMCs thickness at Mg-Al interface from 1.7 µm in FSLW to 1.1 µm in UVeFSLW. The exerted UV increased the horizontal materials flow ability, and decreased the upward flow ability, which resulted in the increase of effective sheet thickness/effective lap width from 2.01/3.70 mm in FSLW to 2.04/4.84 mm in UVeFSLW. Therefore, the ultrasonic vibration improved the tensile shear strength of Mg-to-Al lap joints by 18 %.